2009
DOI: 10.1007/s00268-009-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Morbidity and Mortality in Oncologic Gastric Surgery with the Application of POSSUM, P‐POSSUM, and O‐POSSUM

Abstract: The control systems of risk allow us continuous evaluation of our results and objective comparison to other teams. Compared with the POSSUM scoring systems, our series showed quality improvement (morbidity and mortality) over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Previous studies have reported various systems for predicting surgical risks. The physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) score [22], modified POSSUM [23], and the estimation of physiological ability and surgical stress (E-PASS) scoring system [24] have been reported to provide reliable predictive scores for mortality and morbidity. However, although these scoring systems predicted total morbidity, they used both preoperative and intraoperative factors to predict postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported various systems for predicting surgical risks. The physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) score [22], modified POSSUM [23], and the estimation of physiological ability and surgical stress (E-PASS) scoring system [24] have been reported to provide reliable predictive scores for mortality and morbidity. However, although these scoring systems predicted total morbidity, they used both preoperative and intraoperative factors to predict postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing experience and hospital volume, post operative adverse events decrease. Table 9 Peru [8] Immamura H et al [9] Sah BK et al [10] Luna A et al [11] Gong DJ et al [12] Gil-Rendo A et al [13] Díaz de Liaño A et al [14] Kostić Z et al [15] Biffi R et al [16] Kan YF et al [17] Orsenigo E et al [18] Shrikhande SV et al [19] Number compares the surgical load and complication rates at various centers. Many specialized centers in the west [5,6,7,8] are now reporting low post operative complications comparable to that in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Both can be used for risk-adjusted surgical audit [ 57 ] 2005 High risk patients undergoing surgery p-POSSUM predicted mortality well but POSSUM over-predicted mortality [ 58 ] 2006 elective and emergency laparotomy It is a useful predictor of morbidity and mortality [ 59 ] 2007 General surgery M-POSSUM correlates better with postoperative complications and mortality than POSSUM [ 60 ] 2008 cases of ileal perforations Significant correlation between POSSUM score and postoperative complications and deaths [ 61 ] 2009 Patients undergoing emergency laparotomy P-POSSUM predicts mortality better than POSSUM. Exponential method is better than linear regression analysis [ 62 ] 2009 Unresectable pancreatic cancer during exploratory laparotomy POSSUM scoring system is an independent predictor of survival in multivariate analysis [ 63 ] 2009 oncologic gastric surgery Mortality lower than that predicted by POSSUM and higher than that predicted by P-POSSUM [ 64 ] 2010 patients undergoing emergency surgery ASA grade and POSSUM scores were the better predictors of mortality than EWS, APACHE II, and age [ 65 ]. 2010 general surgical laparotomy P-POSSUM is a better overall predictor of mortality than POSSUM [ 11 ].…”
Section: Surgical Audit Scoring Systemsmentioning
confidence: 99%